Irisin protects against endothelial injury and ameliorates atherosclerosis in apolipoprotein E-Null diabetic mice. Issue 2 (December 2015) - Lu, Junyan; Xiang, Guangda; Liu, Min; Mei, Wen; Xiang, Lin; Dong, Jing
Abstract: Objective: The circulating irisin increases energy expenditure and improves insulin resistance in mice and humans. The improvement of insulin resistance ameliorates atherosclerosis. Therefore, we hypothesized that irisin alleviates atherosclerosis in diabetes. Methods: Endothelial function was measured by acetylcholine-induced endothelium-dependent vasodilation using aortic rings in apolipoprotein E-Null (apoE −/− ) streptozotocin-induced diabetic mice. Atherosclerotic lesion was evaluated by plaque area and inflammatory response in aortas. In addition, the endothelium-protective effects of irisin were also further investigated in primary human umbilical vein endothelial cells (HUVECs) in vitro . Results: The in vivo experiments showed that irisin treatment significantly improved endothelial dysfunction, decreased endothelial apoptosis, and predominantly decreased atherosclerotic plaque area of both en face and cross sections when compared with normal saline-treated diabetic mice. Moreover, the infiltrating macrophages and T lymphocytes within plaque and the mRNA expression levels of inflammatory cytokines in aortas were also significantly reduced by irisin treatment in mice. The in vitro experiments revealed that irisin inhibited high glucose-induced apoptosis, oxidative stress and increased antioxidant enzymes expression in HUVECs, and pretreatment with LY294002, l -NAME, AMPK-siRNA or eNOS-siRNA, attenuated the protection of irisin on HUVECs apoptosis induced by high glucose. In addition, the in vivo and in vitro experiments showed that irisin increased the phosphorylation of AMPK, Akt and eNOS in aortas and cultured HUVECs. Conclusions: The present study indicates that systemic administration of irisin may be protected against endothelial injury and ameliorated atherosclerosis in apoE −/− diabetic mice. The endothelium-protective action of irisin was through activation of AMPK-PI3K-Akt-eNOS signaling pathway. Irisin could be therapeutic for atherosclerotic vascular diseases in diabetes. Highlights: Irisin protects against diabetes-induced endothelial damage. Irisin ameliorates atherosclerosis in apolipoprotein E-null mice. The endothelium-protective action of irisin was through AMPK-PI3K-Akt-eNOS pathway.